Realization of trilingual politics in education system of the Republic of Kazakhstan - Amanbayeva, G.Yu.; Meirbekova, M.K. (Вестник Карагандинского университета, 2017)
In the article problems of formation and development of the country are considered in adoption of project trilingual in education system.Also about mechanism of preparation polylingual teaching staff. Number of the positive facts which precede to success country from the different parties and industries of policy is noticed. There are psychological and linguo – pedagogical character tasks which are connected with specific features of listeners in the education process. Authors envisage trilingual education as the productive mechanism of training of the younger generation for functioning in the conditions of the independent and competitive country.
Қазақстан Республикасында білім беру жүйесінде үштілділік саясатының іске асырылуы
Реализация политики трехъязычия в системе образования Республики Казахстан
Keywords: trilingual education; multilingualism; trinity of languages; sociolinguistics; linguo-pedagogical teaching staff